Tensile properties of polyamide 12 / black with 10wt.% copper samples manufactured by laser powder bed fusion (Transactions on Additive Manufacturing Meets Medicine, 2021)
In laser powder bed fusion (L-PBF) of polymers, a proven material for biomedical applications is Polyamide 12 (PA 12) that is used for production of functional prototypes and end-use parts. The aim of this study is to investigate properties of in situ copper-modified polyamide (Sintratec PA12/B) at 10 wt.% Cu by L-PBF. Polymer-metal composites test samples were evaluated for their porosity, Cu distribution and tensile properties.
Keywords: Laser powder bed fusion; polymers; functionalization; biomedical applications